Effect of high-frequency (5Hz) rTMS stimulating left DLPFC combined with galantamine on cognitive impairment after ischemic stroke and serum homocysteine and neuron-specific enolase - Hu, Guojin; Zhang, Li; Sun, Xiuli; Wang, Lin; Xu, Qian; Li, Qin; Huang, Wei; Xiao, Yao (Frontiers in Neurology, 2024)
Objective: To investigate the efficacy of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) combined with galantamine in patients with cognitive impairment after stroke and its effect on serum homocysteine (Hcy) and neuron-specific enolase (NSE) levels. Methods A total of 90 patients with cognitive impairment after the first ischemic stroke were enrolled. They were randomly divided into rTMS+ cognitive rehabilitation group, Galantamine + cognitive rehabilitation group, and rTMS+ Galantamine + cognitive rehabilitation group. All groups received routine medical treatment and limb rehabilitation treatment. The rTMS stimulation site was the left dorsolateral prefrontal cortex(left DLPFC), the magnetic stimulation frequency was 5Hz, the magnetic stimulation intensity was 80% of the motor threshold level, and 3000 pulses were given every day.The Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA, Fugl-Meyer scale, and modified Barthel index, as well as rehabilitation scale and serum NSE and Hcy were evaluated before and after treatment (after 4 weeks). Results: After 4 weeks of treatment, the scores of MMSE, MoCa scale, Fugl-Meyer scale, and modified Barthel index in the three groups were significantly higher than those before treatment (all P<0.05), while the serum NSE and Hcy levels of the three groups were decreased. rTMS+ Galantamine + cognitive rehabilitation group had higher scale scores, and the difference between the three groups was statistically significant compared with the other two groups (all P<0.05). Conclusion: Cognitive rehabilitation combined with HF-rTMS and galantamine could improve the cognitive function of patients to the greatest extent, promote the recovery of physical activity, improve the self-care ability of daily life, and effectively reduce the serum HCY and NSE levels in patients with cognitive impairment after stroke. No randomized controlled trials of similar combination treatments have been reported.The better therapeutic effect may be related to the fact that galantamine combined with repetitive transcranial magnetism can activate the brain cholinergic system more extensively,promote brain neural remodeling through long-term potentiation and inhibit local neuroinflammatory responses in brain injury.